PRIMARY CLASS TEACHER IN IMPROVING EDUCATIONAL EFFICIENCY PLACE - Sattorova Muattar Abduraupovna, (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, the management of the educational system, improving the effectiveness of education the role of the teacher, the issue of education, the duties of the teacher in providing knowledge to students, the leader responsibility, about the formation of students' knowledge skills in the educational process information is provided.